2020
DOI: 10.3390/rs12020340
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Boundary Layer Over an Urban Continental Site Based on 10 Years of Active Remote Sensing Observations in Warsaw

Abstract: Atmospheric boundary layer height (ABLH) was observed by the CHM15k ceilometer (January 2008 to October 2013) and the PollyXT lidar (July 2013 to December 2018) over the European Aerosol Research LIdar NETwork to Establish an Aerosol Climatology (EARLINET) site at the Remote Sensing Laboratory (RS-Lab) in Warsaw, Poland. Out of a maximum number of 4017 observational days within this period, a subset of quasi-continuous measurements conducted with these instruments at the same wavelength (1064 nm) was carefully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 82 publications
1
36
1
Order By: Relevance
“…The uncertainty of extinction-derived ÅE ABL (355/532) is less than 30 %. The uncertainty of the ABLH retrieval from PollyXT lidar is ±70 m (Wang et al, 2019).…”
Section: Methodology Of Lidar Product Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty of extinction-derived ÅE ABL (355/532) is less than 30 %. The uncertainty of the ABLH retrieval from PollyXT lidar is ±70 m (Wang et al, 2019).…”
Section: Methodology Of Lidar Product Retrievalmentioning
confidence: 99%
“…used the latter method for the first retrievals of the ABLH in Warsaw. Wang et al (2019) reported that the wavelet covariance transform method (WCT) is the most optimal technique for ABLH retrieval for the PollyXT lidar data in Warsaw. As for the WCT method applied in our study, the covariance transform W f of the Haar wavelet function h, is defined as in Eq.…”
Section: Methodology Of Lidar Product Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, at night-time in central Europe, convection processes are not expected-typical night-time boundary layer height over Warsaw in August is <1.5 ± 0.2 km a.g.l. [54]. However, during the daytime, the top of the boundary layer can reach 2.9 ± 0.6 km a.g.l.…”
Section: Active Remote Sensing Observations From Satellites and At Grmentioning
confidence: 95%
“…For the retrieval of the boundary layer height two classic methods were used: the Haar wavelet method as described in [52] and the gradient method as shown in [53], which are applied on the range and background corrected lidar signals at three elastic wavelengths. The boundary layer height is computed as the mean height of the three, that allows estimating the uncertainty of the retrieval which is in general below ±40 m [54].…”
Section: Derivation Of Optical Properties From Raman Lidarmentioning
confidence: 99%